Riset sebagai Ujung Tombak Keberhasilan Program Public Relations - Ike Devi Sulistyaningtyas (FISIP Universitas Atma Jaya Yogyakarta, 2010)
Abstract : Public Relations encompasses basically the management and communications function between organizations and public. The important thing of the public relations management is research, because Public Relations program is started from research and after all the programs done. It is also using research to find the output and outcome. The point is how to gain successful of Public Relations program depend on how to use research.